Case Report: Newborn with Anorectal Malformation - Agrawal, Triptee; Rimal, Hem Sagar (Birat Journal of Health Sciences, 2018)
Anorectal malformations are defined by the relationship of the rectum to the sphincter complex and can be classified as high and low anomaly based on whether meconium is present or absent, presence of dimple, anocutaneous reflex, sacral abnormality or presence of meconium in urine. The diagnosis should be made in the delivery room by inspecting the perineum. Meconuria with absence of anal opening invariably indicates a high malformation which requires a colostomy in the newborn period. Low malformations do not become evident until 24 hours when the meconium may show up in the perineal fistula. These defects can be managed by a perineal anoplasty without a colostomy in the newborn period. A prone cross table lateral shoot abdominal film is required if clinical information at 24 hours is insufficient to decide whether a colostomy is needed. We present a case of newborn, day 4 of life, who did not pass meconium since birth, had abdominal distension, vomiting, poor feeding and lethargy since last 2 days. Anal area showed pigmentation with presence of median raphe, anal dimple and slightly formed anal opening. Baby was initially thought as a case of low type imperforate anus. On further evaluation, was found to have meconuria too. Invertogram done showed high type defect. Rest of the examination was normal. Supportive therapy was initiated and baby underwent transverse loop colostomy for high type imperforate anus on day 5 of life. So it is always advisable to confirm the type of anorectal malformation both clinically and by doing required investigation before deciding for any operative intervention like colostomy or anoplasty, as clinical examination and investigation may not correlate in all occasions. Evaluation should also include screening out for associations and other sacral anomalies. BJHS 2018;3(2)6: 500-503.